2020
DOI: 10.3389/fimmu.2019.03077
|View full text |Cite
|
Sign up to set email alerts
|

CpG-Recoding in Zika Virus Genome Causes Host-Age-Dependent Attenuation of Infection With Protection Against Lethal Heterologous Challenge in Mice

Abstract: Experimental increase of CpG dinucleotides in an RNA virus genome impairs infection providing a promising approach for vaccine development. While CpG recoding is an emerging and promising vaccine approach, little is known about infection phenotypes caused by recoded viruses in vivo. For example, infection phenotypes, immunogenicity, and protective efficacy induced by CpG-recoded viruses in different age groups were not studied yet. This is important, because attenuation of infection phenotypes caused by recode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(87 citation statements)
references
References 70 publications
(131 reference statements)
5
82
0
Order By: Relevance
“…Efficacy of the CpG-recoded influenza virus vaccine has been demonstrated in mice; we also showed full protection evoked by CpG-recoded Zika virus (ZIKV) vaccine candidates in mice challenged with lethal heterologous ZIKV [7].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Efficacy of the CpG-recoded influenza virus vaccine has been demonstrated in mice; we also showed full protection evoked by CpG-recoded Zika virus (ZIKV) vaccine candidates in mice challenged with lethal heterologous ZIKV [7].…”
Section: Introductionmentioning
confidence: 62%
“…In silico recoding and recovery of CpG-modified ZIKV variants were previously described [7]. The MUTATE SEQUENCES program in the SSE 1.3 software package (Peter Simmonds, University of Oxford, Oxford, UK) [28] was used to modify the sequence of the contemporary Asian ZIKV H/PF/2013 strain [GenBank: KJ776791.2] [29] and to generate variants with increased CpG numbers in regions encoding envelope (E) and nonstructural 1 (NS1) proteins ( Figure 1).…”
Section: Design and Recovery Of Cpg-recoded Zikv Variantsmentioning
confidence: 99%
“…Apart from this, CpG oligodeoxynucleotides (ODNs) are known to act as adjuvants and are already established as a potent stimulator for host immune system (Campbell, 2017; Becker, 2005; Yuan, 2017; Singh et al, 2016; Yu et al, 2018). Moreover, recent studies conducted on influenza A genome and Zika virus genome has shown that by increasing the CpG dinucleotides in viral genome, impairment of viral infection is observed (Gaunt et al, 2016; Trus et al, 2020). Our result showed that the presence of conserved CpG islands in Nps1 and N protein across 245 genomes of SARS-CoV-2 indicated their role in pathogenesis and can be targeted by Zinc Finger Antiviral Proteins or exploited to design CpG-recoded vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that experimental increase in the pools of CpG dinucleotides in CpG-deficient viral genomes may lead to significant decrease in viral replication and virulence [59][60][61]. Thus, it may suggest that m 5 C RNA methyltransferases may play an important role during the recognition of viral CpG and the inhibition of replication process of selected types of viruses.…”
Section: Host-based Methylation Of the Fifth Position Of Cytosine Resmentioning
confidence: 99%